Association Among the Gut Microbiome, the Serum Metabolomic Profile and RNA m6A Methylation in Sepsis-Associated Encephalopathy - Wang, Hui; Wang, Qing; Chen, Jingjing; Chen, Cunrong (Frontiers in Genetics, 2022)
Objective: To investigate the relationship among the gut microbiome, serum metabolomic profile and RNA m6A methylation in patients with sepsis-associated encephalopathy (SAE), 16S rDNA technology, metabolomics and gene expression validation were applied. Methods: Serum and feces were collected from patients with and without (SAE group and non-SAE group, respectively, n = 20). The expression of serum markers and IL-6 was detected by enzyme-linked immunosorbent assay (ELISA), and blood clinical indicators were detected using a double antibody sandwich immunochemiluminescence method. The expression of RNA m6A regulator were checked by Q-RTPCR. The gut microbiome was analyzed by 16S rDNA sequencing and the metabolite profile was revealed by liquid chromatography-mass spectrometry (LC-MS/MS). Results: In the SAE group, the IL-6, ICAM-5 and METTL3 levels were significantly more than those in the non-SAE group, while the FTO levels were significantly decreased in the SAE group. The diversity was decreased in the SAE gut microbiome, as characterized by a profound increase in commensals of the Acinetobacter, Methanobrevibacter, and Syner-01 genera, while depletion of opportunistic organisms of the Anaerofilum, Catenibacterium, and Senegalimassilia genera were observed in both groups. The abundance of Acinetobacter was positively correlated with the expression of METTL3. The changes between the intestinal flora and the metabolite profile showed a significant correlation. Sphingorhabdus was negatively correlated with 2-ketobutyric acid, 9-decenoic acid, and L-leucine, and positively correlated with Glycyl-Valine; [Eubacterium]_hallii_group was positively correlated with 2-methoxy-3-methylpyazine, acetaminophen, and synephrine acetonide. Conclusion: The gut microbiota diversity was decreased. The serum metabolites and expression of RNA m6A regulators in PBMC were significantly changed in the SAE group compared to the non-SAE group. The results revealed that serum and fecal biomarkers could be used for SAE screening.